Clinical report of six-month follow-up after cementing PEEK crown on molars - Kimura, Hitomi; Morita, Koji; Nishio, Fumiko; Abekura, Hitoshi; Tsuga, Kazuhiro (Scientific reports, 2022)
We conducted a six-month clinical follow-up on computer-aided design/computer-aided manufacturing-fabricated molar polyetheretherketone PEEK crowns to investigate their therapeutic effect. Only the PEEK crowns were examined as our study focused on short-term clinical evaluation of the new PEEK material. Twenty-three cases of PEEK crowns placed on the molars of 20 subjects (7 males and 13 females, mean age: 60.6 ± 14.2 years) were included in the study. The evaluation items were the condition of the crowns at the time of cementation and after six months, patient satisfaction, masticatory ability, and occlusal force. Mann–Whitney U tests with a significance level of 5% were used to examine the difference in glucose concentration by masticatory ability, occlusal pressure, and occlusal force, with and without PEEK crowns. The occlusion, margin fit, and contact of all 23 cases at the time of cementing were good. Six months after cementation, there was no crown desorption, fracture or crack, and prosthodontics was not needed in the 22 cases (one patient dropped out). No wear of the dental antagonist was observed. Patient satisfaction was generally high. There was no significant difference in masticatory ability between the groups with and without PEEK crowns. The subject's occlusal force was within the normal range. PEEK crowns used on molars can replace metal crowns and hold promise for an appropriate and effective treatment.